Ensino de programação para crianças utilizando robôs programáveis - Guida, Sérgio Torres (2021)
With the advancement of technology, the field of education is increasingly using technological equipment such as digital whiteboards and mobile devices to help on the learning process. The use of robots in class can provide teachers a variety of possibilities of subjects to teach such as electronic circuits, physics and programming. This project aims to construct a robot that can be used to teach basic concepts of programming. The app which controls the robot was developed with availability to Android and iOS devices. The app lets the user utilize different commands to make the robot accomplish specific tasks such as walking through a specific path or drawing geometric shapes. The communication between the robot and the app is made using bluetooth. The following technologies were used to create the robot and the app: Arduino, Dart and Flutter.